Upaya Kebijakan Pendidikan di Mesir - Ummul Rahmah; Mislaini Mislaini; Syakinatul Jannah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Education Policy in Egypt: Improving Quality through Reform. This research analyzes Egypt's post-2011 revolution education policy, with a focus on primary and secondary education reform strategies. This research aims to identify effective policies in improving the quality of educatio The research results show that curriculum development, teacher training, and infrastructure improvement are strategies that have the potential to improve equality and the quality of educatio in Egypt. These findings contribute to the understanding of effective education policies in developing countries.